EXPLORING CONSUMER INTENTION FOR FUNCTIONAL FOOD PRODUCTS IN HUNGARY: THE ROLE OF HEALTH CONSCIOUSNESS, NUTRITIONAL KNOWLEDGE AND ATTITUDES - Ghaith, Abrar (Applied Studies in Agribusiness and Commerce, 2024)
Background: The potential health advantages of functional food products have increased their appeal. Their reception and implementation are greatly influenced by consumer attitudes and purchasing intentions. The Theory of Planned Behavior (TPB) is used in this study to examine how attitudes toward and intentions to buy functional food products in Hungary are influenced by health consciousness (HC) and nutritional knowledge (KN). Methods: From March to May 2023, 396 adult Hungarian volunteers took part in an online survey. The poll measured respondents’ intentions to buy functional food products as well as their health consciousness, nutritional knowledge, attitudes, and subjective norms (SN). Through pilot research, the questionnaire’s reliability and validity were determined. Multiple regression analyses, one-sample t-tests, and Cronbach’s alpha were all included in the statistical analysis. Results: The majority of participants were female, working students. In support of hypotheses H1 and H2, health consciousness significantly influenced attitudes and purchase intentions. H3 and H4 are supported by the findings that nutritional knowledge strongly influenced attitudes and purchase intentions. Both perceived behavioral control and subjective standards had a beneficial impact on purchase intentions supporting H5 and H6. Conclusion: This study provides important insights into Hungarian consumers’ preferences for functional food items. It highlights the beneficial effects of health awareness, information, attitudes, arbitrary standards, and perceived behavioral control on buying intentions. It was discovered that attitudes play an important role in mediating the link between nutritional knowledge, health consciousness, and purchase intentions. It was discovered that attitudes play an important role in mediating the link between nutritional knowledge, health consciousness, and purchasing intentions. The dynamic functional food market’s marketers and legislators should take these findings seriously. The subtleties of these attitudes and their implications for promotional tactics can be explored in greater detail in future research. Promoting healthier food options and informing policy and marketing decisions require an understanding of consumer perceptions and behaviors.